Effects of Noise Stress on Body Weight and Adrenal Gland Weight of Male Wistar Rats: Effects of Noise Stress on Body Weight and Adrenal Gland Weight of Male Wistar Rats - Mehra, Ravinder Kr (International Journal of Pharmaceutical & Biological Archive, 2020)
The present study was designed to investigate the effects of varying intensities of noise stress onto the body and adrenal gland weight (absolute) of 17 weeks old (291–296) gram (g) Wistar rat. Animals were exposed to varying intensity of noise, i.e., 60 dB (Decibel), 80 dB, 100 dB, 120 dB, and 140 dB for 1 h (h)/day for 30 days. The dose of different noise intensities was delivered through a special fabricated noise chamber which had provided all daily needs of animal-like oxygen, food, and water. Food and water consumption behavior was recorded on 1st, 14th, and 29th days and body weight change recorded on 1st, 15th, and 30th days after the exposure of noise stress. Absolute adrenal glands weight was recorded on the 30th day. The results of the present study showed that the food, water consumption behavior, and body weight (g) of the experimental group EG1 (60 dB), EG2 (80 dB), EG3 (100 dB), EG4 (120 dB), and EG5 (140 dB) were found to be significantly (P < 0.001) decreased during 1st–14th days and during 15th–30th days a recovery which were observed in food, water consumption, and in body weight of the EG1 (60 dB), EG2 (80 dB), and EG3 (100 dB). A percentage (%) decrease was found, i.e., 0.76, 0.37, 3.87, 25.89, and 30.06% in body weight of EG1 (60 dB), EG2 (80 dB), EG3 (100 dB), EG4 (120 dB), and EG5 (140 dB) experimental groups, respectively.